THEORETICAL LAW ZONE OF CORRUPTION RISKS IN THE SPHERE OF DEFENSE - Піскун, Іван Іванович; Левчук, Віктор Дмитрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the goal of the article is to research the theoretical law zone of corruption risks in the sphere of defense. Methods: the methodology of the research is based on general scientific methods of cognition as well as specific domain knowledge which helps determine the objective patterns of the theoretical law problem of corruption, particularly in the defense sector. Results: the basic principle of the given research is the development of theoretical law constructions taking into account the new national juridical ideology of anthropocentrism, the idea of humanization of legal administrative regulation and meeting the requirements of strict observance of the anti-corruption legislation in the sphere of defense as well as in the sphere of national security of Ukraine. Discussion: contemporary informational globalization in the sphere of defense presuppose not only the appearance of new legislative mechanisms but the necessity to change the paradigm of juridical thought and reconsider the theoretical foundations of law in general. This, in its turn, foregrounds the need for constant identification of the reasons for the juridical evolution of corruption risks in the sphere of defense and the elaboration of ways of gradual development of anti-corruption legislation in the national security segment.